The Effect of Phoenix Dactylifera on Uterine Contraction in Labor - Kartika, Dinda; Kundarti, Finta Isti; Mediawati, Mika; Setyarini, Didien Ika (Poltekkes Kemenkes Riau, 2023)
Cases of prolonged labor in women labor in the world are still relatively high. Inadequate uterine contractions are the leading cause of complications of maternal death worldwide. This study aimed to analyze the Effect of Phoenix Dactylifera on uterine contractions in birthing mothers. The method applied in this research was an experimental Pretest posttest control group design. In this study, there were 60 samples, which were divided into two groups. The Paired t-test results on uterine contractions during the pretest-posttest in the intervention group showed significant results, namely a value of 0.000. In the control group, uterine contractions during the pretest-posttest showed an AP value of 0.090. Uterine contractions increased (adequate) after the mothers were given dates.